Towards Optimization of μ-Injection Molding Process for a New V-Shaped Geometrical Component Using X-ray CT-Based Quality Characterization - Jitendra Singh Rathore; Giovanni Lucchetta; Simone Carmignato (Journal of Manufacturing and Materials Processing, 2019)
The influence of micro-injection molding process parameters on a molded component’s quality is very prominent. Depending on the functional performance of the part, the desired quality is defined by several criteria which may include dimensional tolerances, shrinkage/warpage, fiber characteristics, and internal defects. A correlation of process parameters with the defined quality attributes needs to be investigated for a new geometrical component. In this work, a micro-component with a new V-shaped geometry is chosen, as this type of geometry finds potential applications in the medical industry. The parts are manufactured with polyoxymethylene resin with a full-factorial design of experimental plan with investigating parameters of mold temperature, melt temperature, injection speed, and packing pressure. The number of internal pores and amount of volumetric shrinkage are identified as the critical quality criteria and the effect of the process parameters is studied with respect to those criteria. The measurement results indicated that the presence of pores is inevitable within the chosen process window; however, the amount can be minimized with careful selection of process settings. Moreover, the statistical analyses demonstrated the significance levels of the process parameters.